THE IMPACT OF MANDATORY COVID-19 VACCINATION POLICY IN INDONESIA: LEGAL AND BIOETHICS PERSPECTIVES (UUM Journal of Legal Studies, 2024)
The Indonesian government has made significant efforts to provide vaccines as a solution to prevent the transmission of COVID-19. However, while some individuals have received the vaccine, others have refused due to fear and doubts about its safety and halal status. The implementation of a policy mandating COVID-19 vaccination by the government has both advantages and disadvantages. According to the policy, individuals who refuse to vaccinate will face administrative and criminal sanctions. Therefore, this research aims to provide a summary of the mandatory COVID-19 immunization policy, particularly in Indonesia, from both a legal and bioethical perspective. A legal approach and normative bioethical principles were used to analyze applicable legal norms and bioethical principles, utilizing literature research. Legal materials included Law Number 4 of 1984 concerning Outbreaks of Infectious Diseases, Law Number 36 of 2009 concerning Health, Article 28H of the 1945 Constitution of the Republic of Indonesia, and Article 34 paragraph (3) of the 1945 Constitution. Meanwhile, the source of bioethical data used was the Universal Declaration of Bioethical and Human Rights. Instead of implementing a mandatory vaccination policy containing elements of criminal sanctions, the government should actively engage with the community and analyze why there are still doubts regarding COVID-19 vaccination. This would be a more effective and humane strategy for providing health protection. A mandatory COVID-19 vaccination policy should be based on a comprehensive strategy and ongoing efforts, taking into account legal and bioethical aspects.